The Role of Forests in Providing Ecosystem Services for Environmental Resilience - Jelibseda Jelibseda; Abdul Razak; Nurhasan Syah; Skunda Diliarosta (Science and Environmental Journal for Postgraduate, 2024)
Increasing atmospheric CO₂ concentrations contribute to climate change, with industrial and economic activities accelerating greenhouse gas emissions. However, human-induced emissions also stem from deforestation, where forests act as carbon sinks through photosynthesis but release carbon when cut down. Forests play a crucial role in mitigating climate change by storing carbon, and their restoration can enhance their carbon-absorbing capacity. This research, based on a literature review, examines the role of forests in providing ecosystem services for environmental resilience, utilizing sources from Google Scholar, Elsevier, and Science Direct. Forests and agroforestry systems contribute to food and nutritional security, providing various products like food, medicine, and materials for construction and fuel. However, forest fires and logging disrupt these contributions. Forests support livelihoods by offering diverse products and ecosystem services. Managing forest gaps, which influence biodiversity and nutrient cycles, is crucial for forest ecology.